A Novel Robotic-Assisted Rehabilitation System for Elbow Fracture: Design and Full-Cycle Rehabilitation Strategy - Qianze Helian; Jiade Chang; Zhiyuan He; Tao Sun (IEEE Transactions on Neural Systems and Rehabilitation Engineering)
Postoperative rehabilitation is critical for restoring elbow function following fractures, yet current approaches face significant limitations. Manual rehabilitation lacks precision and relies heavily on subjective experience, while existing robotic systems, primarily designed for neurological rehabilitation, fail to provide essential joint traction capabilities. In this paper, a novel robotic system integrating elbow rotation and traction functions (ERT-Robot) is proposed to provide full-cycle rehabilitation training. The system features an adaptive rotation mechanism that accommodates upper limb biomechanics and a traction mechanism for soft tissue stretching, ensuring wide patient applicability. A full-cycle rehabilitation protocol incorporating three therapeutic modalities: reciprocating passive training, active range of motion training, and muscle strength training, is introduced to address diverse clinical needs across all rehabilitation phases. Experimental validation involving six healthy subjects demonstrated that the robotic system significantly increased both horizontal and vertical olecranon displacements compared to natural arm rotation. Quantitative analysis showed minimal differences between manual and robot-assisted rehabilitation, with mean displacement variations of merely 1.33% (horizontal) and 7.78% (vertical), demonstrating clinically comparable performance. In addition, experimental results in three rehabilitation modalities confirmed the system’s feasibility and efficiency for postoperative elbow fracture management.